2002
DOI: 10.1128/jcm.40.4.1146-1151.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Pneumocystis carinii f. sp. hominis Based on Variations in Nucleotide Sequences of Internal Transcribed Spacers of rRNA Genes

Abstract: A variety of genes have been used to type Pneumocystis carinii. In the present study, nucleotide sequence variations in the ITS1 and ITS2 internal transcribed spacer (ITS) regions of the rRNA genes were used to type Pneumocystis carinii f. sp. hominis DNA obtained from the lungs of 60 human immunodeficiency virus-infected individuals. These regions were amplified by PCR, cloned, and sequenced. Multibase polymorphisms were identified among samples. Several new genotypes are reported on the basis of the nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…The most prevalent haplotype worldwide, including Australia, is Eg, accounting for 23% of all published combinations (10,13,24,26,27,30). Unlike previous studies, a novel genotype (Isyd2) was found to be the second most common Australian haplotype, occurring in 18% of our samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most prevalent haplotype worldwide, including Australia, is Eg, accounting for 23% of all published combinations (10,13,24,26,27,30). Unlike previous studies, a novel genotype (Isyd2) was found to be the second most common Australian haplotype, occurring in 18% of our samples.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence gaps (caused by insertions and deletions in the alignment) are considered missing data, thereby greatly reducing the probability of incorrect and inaccurate phylogenies in the tree and hence faulty interpretations of global haplotype relationships. In addition, several ITS1 (n ϭ 12) and ITS2 (n ϭ 18) types were not included in this analysis, as the haplotypes formed by these ITS genotypes have not been detailed to allow inclusion (24,29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the high level of polymorphism in the composition of the ITSrDNA locus, several molecular epidemiological studies have been conducted by using this tool. Analysis of the ITS regions of the nuclear rRNA operon for different parasites has demonstrated the utility of this marker in detect genetic diversity and the association of this with several epidemiological aspects (9,26) The present study also indicates that most of the genotypes are specific to some geographic areas (e.g., genotype B1 contains isolates from one geographic location, in Espírito Santo, that were collected over a distinct period of time [between 1982 and 1995]), showing the importance of clonal dissemination versus sexual reproduction for this organism in nature, at least occurring in some regions. The stability of this genotype adapting to some environmental modifications through years in the same area is a clear proof of the aforementioned statement.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 30 ITS1 genotypes and 40 ITS2 genotypes with more than 90 haplotypes (combinations of ITS1 and ITS2 types) have been described worldwide, based on two different but similar typing systems (8,26). Some ITS haplotypes are globally more common, and coinfections with multiple types of P. jirovecii often occur (4,8,11,15,17,25,26). Although these typing systems have been useful, questions have been raised about the extensive polymorphism and stability of the ITS locus and its use for the genotyping of P. jirovecii.…”
mentioning
confidence: 99%